1998
DOI: 10.1021/bi981794l
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Kinetic Determinants of Aldehyde Reduction by Aldose Reductase

Abstract: Aldose reductase (AR) is a member of the aldo-keto reductase superfamily. Due to its ability to catalyze the formation of sorbitol from glucose during hyperglycemic and hypertonic stress, the aldose-reducing property of AR has been accepted as its main physiological and pathological function. Nonetheless, AR is a poor catalyst for glucose reduction and displays active-site properties unexpected of a carbohydrate-binding protein. We, therefore, examined the catalytic properties of AR with a series of naturally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
146
0
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 167 publications
(162 citation statements)
references
References 49 publications
(70 reference statements)
9
146
0
5
Order By: Relevance
“…AR reduces one of the most abundant and toxic lipid aldehydes, 4-hydroxy-trans-2-nonenol (HNE), to 1, 4-dihydroxynonene (DHN) and its glutathione conjugate, GS-HNE, to GS-DHN (20,21). We have demonstrated that AR plays a pivotal role in the proliferation of vascular smooth mus-cle cells, apoptosis of vascular endothelial cells and restenosis of rat carotid artery (17,18,22).…”
mentioning
confidence: 99%
“…AR reduces one of the most abundant and toxic lipid aldehydes, 4-hydroxy-trans-2-nonenol (HNE), to 1, 4-dihydroxynonene (DHN) and its glutathione conjugate, GS-HNE, to GS-DHN (20,21). We have demonstrated that AR plays a pivotal role in the proliferation of vascular smooth mus-cle cells, apoptosis of vascular endothelial cells and restenosis of rat carotid artery (17,18,22).…”
mentioning
confidence: 99%
“…Extensive investigations show that AR is a broad specificity enzyme that catalyzes the reduction of a wide range of aldehydes. Its kinetic properties are optimized such that the energetics of substrate binding do not contribute to the overall catalytic efficiency of the enzyme (1,6). As a result, AR does not display predominant specificity for a unique substrate-product pair; rather, it can reduce several types of aldehydes with nearly equal efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, AR does not display predominant specificity for a unique substrate-product pair; rather, it can reduce several types of aldehydes with nearly equal efficiency. Such behavior confers ideal properties to AR for the reduction of multiple aldehydes, such as the aldo-keto sugars and the aldehydes generated by lipid peroxidation (3)(4)(5)(6)(7)(8). The broad substrate specificity of the enzyme precludes its ready implication in a unique metabolic pathway and suggests that it may be recruited for tissue-specific use under a variety of metabolic contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, GS-DHN represents 50% of the total conjugate. We have also found that treatment with AR inhibitors prevents the reduction of the conjugate (37,41,64,65) and that in vitro recombinant AR displays high affinity for glutathione conjugates of unsaturated aldehydes (39,40,42). Indeed, for C3 to C9 aldehydes, glutathiolation increases the catalytic efficiency of the enzyme (39).…”
Section: Discussionmentioning
confidence: 72%